Effect of Intellectual Property Rights (IPRS) and absorptive capacity on research & development (R&D): empirical evidences in developing economies - Mohamad, Asuantri; Mhd Bani, Nor Yasmin (Zes Rokman Resources, 2018)
This study investigates the impact of IPRs protection and absorptive capacity on research and development (R&D) expenditure in developing economies. Utilizing panel data from 2009-2014 for a sample of 41 developing countries and applying the SystemGMM estimator, we reached important conclusions. The estimated results show that IPRs protection has a positive and significant impact on R&D, however, absorptive capacity does not have a significant impact on R&D when estimated separately. The effect changes when we consider the interaction of the both variables, such that there exists a negative relationship between the interaction variables. This indicates that stronger level in IPRs protection hinders R&D efforts in the country with an inadequate level of absorptive capacity. The results also imply that both appropriate levels of IPRs protection and adequate level of absorptive capacity are necessary to increase R&D activities in the host developing countries.